THEORETICAL STUDY ON THE HYDROGEN BONDING INTERACTIONS IN PARACETAMOL-WATER COMPLEXES - Xu, Meifang; Zhang, Bohai; Wang, Qi; Yuan, Yuan; Sun, Le; Huang, Zhengguo (Journal of the Chilean Chemical Society, 2018)
The paracetamol–water (PA–H2O) complexes formed by hydrogen bonding interactions were investigated at the MP2/6–311++G(d,p) level. Six PA–H2O complexes possessing various types of hydrogen bonds (H–bonds) were characterized by geometries, energies, vibrational frequencies. Natural bond orbital (NBO), quantum theory of atoms in molecules (QTAIM) and the localized molecular orbital energy decomposition analysis (LMO–EDA) were performed to explore the nature of the hydrogen–bonding interactions in these complexes. The intramolecular H–bond formed between the methylene and carbonyl oxygen atom of paracetamol is retained in most of complexes. The H–bonds in PW1 and PW6 are stronger than other H–bonds, moreover, the researches show that both the hydrogen bonding interaction and structural deformation play important roles for the relative stabilities of PA–H2O complexes.